Cell-nonautonomous signaling of FOXO/DAF-16 to the stem cells of Caenorhabditis elegans. - Wenjing Qi; Xu Huang; Elke Neumann-Haefelin; Ekkehard Schulze; Ralf Baumeister (PLoS Genetics)
In Caenorhabditis elegans (C. elegans), the promotion of longevity by the transcription factor DAF-16 requires reduced insulin/IGF receptor (IIR) signaling or the ablation of the germline, although the reason for the negative impact of germ cells is unknown. FOXO/DAF-16 activity inhibits germline proliferation in both daf-2 mutants and gld-1 tumors. In contrast to its function as a germline tumor suppressor, we now provide evidence that somatic DAF-16 in the presence of IIR signaling can also result in tumorigenic activity, which counteracts robust lifespan extension. In contrast to the cell-autonomous IIR signaling, which is required for larval germline proliferation, activation of DAF-16 in the hypodermis results in hyperplasia of the germline and disruption of the surrounding basement membrane. SHC-1 adaptor protein and AKT-1 kinase antagonize, whereas AKT-2 and SGK-1 kinases promote, this cell-nonautonomous DAF-16 function. Our data suggest that a functional balance of DAF-16 activities in different tissues determines longevity and reveals a novel, cell-nonautonomous role of FOXO/DAF-16 to affect stem cells.